Degradable antibacterial starch-based split film fiber for fishing net and preparation method and application thereof

The preparation method of starch-based cracked film fiber modified by montmorillonite-guanidine salt composite has solved the problems of antibacterial and mechanical properties of fishing gear materials, and realized the production of biodegradable fishing nets, which has economic benefits and ecological value.

CN120210990BActive Publication Date: 2026-11-06TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510485070.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2026-11-06
Estimated Expiration
2045-04-17

AI Technical Summary

Technical Problem

Existing fishing gear materials suffer from insufficient antibacterial properties, poor mechanical properties, and difficulty in processing. Furthermore, discarded fishing gear pollutes the environment and hinders the development of fisheries.

Method used

A method of montmorillonite-guanidine salt composite modification was adopted to prepare biodegradable and antibacterial starch-based cracked fiber by compounding starch with PBAT and adding epoxy-based vegetable oil as a crosslinking agent. Fishing net material was prepared by melt extrusion process.

Benefits of technology

It achieves biodegradability and antibacterial properties in fishing net materials, while improving mechanical and processing properties, reducing production costs, and meeting environmental protection policy requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120210990B_ABST
    Figure CN120210990B_ABST
Patent Text Reader

Abstract

This invention discloses a biodegradable antibacterial starch-based split-film fiber for fishing nets, its preparation method, and its application. Belonging to the technical field of fishing net materials, this invention provides a method for preparing biodegradable antibacterial starch-based split-film fibers for fishing nets. The method includes mixing layered nanomaterials with a guanidine salt polymer to obtain a preliminary mixture; drying starch; mixing the dried starch, glycerol, epoxy-based vegetable oil, and the preliminary mixture; then adding poly(butylene adipate / terephthalate) to obtain a premix; heating and plasticizing the premix; granulating to obtain granules; blowing the granules to obtain a film; and slitting the film to obtain split-film fibers. Compared with traditional silk processing, the preparation of split-film fibers using this invention has advantages such as simple equipment, high production efficiency, and low cost. The resulting split-film fibers can be used for twisting and weaving fishing nets and other equipment, enabling fishing nets to possess good mechanical properties while also being biodegradable and antibacterial. This material has good market competitiveness in the fishing market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fishing net materials technology, and particularly relates to a biodegradable antibacterial starch-based cracked fiber for fishing nets, its preparation method and application. Background Technology

[0002] Aquaculture and fishing are pillar industries of current fisheries development, and fishing gear is an indispensable tool in aquaculture. With the development of my country's fisheries, the use of fishing gear has gradually increased. However, discarded fishing gear can cause irreversible damage to the ecological environment and marine life. For example, discarded fishing nets and lines can easily entangle marine life or be ingested by them, leading to their death. Long-term abandonment of discarded fishing gear in the ocean also pollutes the marine ecosystem. Furthermore, it has adverse effects on the marine economy, such as reducing fishery resources and increasing the cost of disposing of discarded fishing gear.

[0003] Based on the national strategy of vigorously promoting ecological and environmental protection, the development of biodegradable materials has effectively responded to the national call. Starch, as a widely available, low-cost, and environmentally friendly polymer raw material, has attracted great attention from researchers. However, the poor mechanical properties of starch products limit its application. Adding other polymer materials to it can effectively improve these shortcomings. Furthermore, starch's strong intermolecular forces, hydrophilicity, and high crystallinity make processing difficult. Polybutylene adipate / terephthalate (PBAT) is a polyester polymer with excellent mechanical properties. Notably, PBAT also possesses biodegradable characteristics. Preliminary research revealed that improving the compatibility of the two is a key issue that needs to be addressed. In addition, regarding performance optimization, adding nanomaterials can effectively alter the mechanical and degradation properties of the substrate. Montmorillonite (MMT) is a low-cost and pollution-free layered nanomaterial, making it a good choice as an additive. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention proposes a biodegradable antibacterial starch-based split-film fiber for fishing nets, its preparation method, and its application. Compared with traditional silk processing, the preparation of the split-film fiber of this invention has advantages such as simple equipment, high production efficiency, and low cost. The resulting split-film fiber can be used to weave fishing nets and other equipment after twisting, enabling the fishing net to have good mechanical properties while also being biodegradable and antibacterial. This material can have good market competitiveness in the fishing market.

[0005] To achieve the above objectives, the present invention provides a method for preparing biodegradable antibacterial starch-based slit-film fibers for fishing nets, comprising the following steps:

[0006] (1) Layered nanomaterials are mixed with guanidine salt polymers to obtain a preliminary mixture;

[0007] (2) Starch drying, the dried starch, glycerin, epoxy vegetable oil and the initial mixture obtained in step (1) are mixed, and then poly(butylene adipate) is added to obtain a premix;

[0008] (3) The premix obtained in step (2) is heated and plasticized, then granulated to obtain granules;

[0009] (4) The granules obtained in step (3) are blown into a film to obtain a thin film, which is then divided to obtain split film fibers.

[0010] Preferably, the layered nanomaterial in step (1) is montmorillonite; the guanidine salt polymer in step (1) is polyhexamethylene guanidine hydrochloride (PHMG).

[0011] Preferably, the drying temperature in step (2) is 60-80°C and the drying time is 5-7 hours.

[0012] Preferably, the mass ratio of the dried starch, glycerol and epoxy vegetable oil in step (2) is 10:3:0.5; the mass of the layered nanomaterial in step (1) accounts for 0.3% of the mass of the premix; the mass of the guanidine salt polymer in step (1) accounts for 1% of the mass of the premix; and the mass of the poly(adipate) / butylene terephthalate in step (2) accounts for 30% to 50% of the mass of the premix.

[0013] Preferably, the starch in step (2) is corn starch; the epoxidized vegetable oil in step (2) is one of epoxidized soybean oil, castor oil and palm oil.

[0014] Preferably, the heating and plasticizing in step (3) is carried out in a twin-screw extruder, and the working temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, 130℃, and the screw speed of the twin-screw extruder is 100~140rpm.

[0015] Preferably, the pelletizing speed in step (3) is 180 rpm.

[0016] Preferably, in step (4), the blown film is blown in a blown film machine. The working temperature of the blown film machine is set to 130℃, 140℃, 145℃, 145℃, 140℃, and 130℃. The speed of the blown film machine is 60 to 100 rpm, and the traction speed of the blown film machine is 3. The width of the segmentation process in step (4) is 4 to 6 mm.

[0017] The present invention also provides the slit-film fibers prepared by the aforementioned preparation method.

[0018] The present invention also provides the application of the slit-film fiber in the preparation of biodegradable antibacterial fishing nets.

[0019] Compared with the prior art, the present invention has the following advantages and technical effects:

[0020] 1. This invention discloses a method for preparing biodegradable antibacterial starch-based split-film fiber based on montmorillonite-guanidine salt composite modification. This method solves the problems of insufficient antibacterial properties, poor mechanical properties, and ghost fishing associated with traditional fishing materials through material compounding. Plasticized starch and PBAT are compounded, and the addition of epoxy-based vegetable oil as a crosslinking agent effectively improves their compatibility, resulting in a material with better mechanical properties. MMT and an antibacterial agent are mixed and then added to starch, followed by mixing with PBAT. The mixture is then extruded and granulated using a melt extrusion process. The granules are then extruded and blown into film to obtain a biodegradable antibacterial starch-based split-film fiber for fishing nets.

[0021] 2. This invention achieves synergistic optimization of material structure and function by combining guanidine salt polymers with montmorillonite. PHMG, as a cationic polymer, inserts into the interlayer of montmorillonite through ion exchange, thereby controlling the interlayer spacing and improving the dispersibility of montmorillonite in the matrix. This operation enables both interlayer spacing control and enhanced dispersibility. Furthermore, the guanidine salt polymer adsorbs onto the cell membranes of microorganisms through electrostatic interactions, disrupting their metabolic activity and achieving an antibacterial effect, effectively reducing pollution from fishing gear.

[0022] 3. This invention uses materials in a specific ratio as blown film raw materials. After extrusion at specific temperatures, times and speeds, it obtains split film fibers with degradable and antibacterial functions, ensuring the smooth blown film production of starch-based split film fibers containing guanidine salt polymers and montmorillonite, and greatly improving the flowability, processability and antibacterial properties of blown film raw materials.

[0023] 4. This invention adds a certain proportion of guanidine salt polymer to the raw materials to give them antibacterial properties; this invention constructs a micro-crosslinked structure by adding epoxy-based vegetable oil, thereby achieving a long-term effective antibacterial effect; this invention adds starch and PBAT to the raw materials to improve the gloss, processability and extrusion quality of the composite material, and greatly improves the softness and appearance quality of starch-based cracked film fibers.

[0024] 5. This invention achieves a balance between processing performance and mechanical strength by optimizing the ratio of starch-based blown film fibers. First, the starch / glycerol ratio is optimized, determining the optimal mass ratio of starch to glycerol to be 10:3. Second, the PBAT proportion is optimized, determining that PBAT accounts for 30%–50% of the total mass. Glycerol acts as a plasticizer, and at this ratio, good mechanical properties can be ensured in continuous blown film production.

[0025] 6. This invention enables continuous production of high-performance film materials. Optimization of twin-screw extrusion and blown film temperatures allows for the continuous production of films with uniform thickness. This invention ensures film regularity, reduces the coefficient of variation, and improves product quality. Compared to traditional monofilament processing methods, the preparation method described in this invention simplifies the process flow, reduces equipment usage, lowers costs, and reduces energy consumption, aligning with current energy conservation and emission reduction policies. Furthermore, this preparation process also boasts high production efficiency. In summary, this invention, through montmorillonite-guanidinium salt polymer composite modification, optimized starch-based material ratios, and innovative blown film processing, prepares a biodegradable, antibacterial starch-based split-film fiber for fishing nets. This preparation method has significant economic and ecological value for use in the fishing industry. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 The images show sample diagrams of the film prepared in Example 1, the film prepared in Comparative Example 1, and the split-film fiber prepared in Example 1, wherein A is the film prepared in Example 1, B is the film prepared in Comparative Example 1, and C is the split-film fiber prepared in Example 1.

[0028] Figure 2 Infrared spectra of montmorillonite, the thin film prepared in Example 1, and the thin films prepared in Comparative Examples 1 to 3;

[0029] Figure 3 The tensile strength measurements are shown for the films prepared in Example 1 and Comparative Examples 1 to 3.

[0030] Figure 4 The antibacterial properties of the films prepared in Example 1 and Comparative Examples 1 to 3 against Escherichia coli are shown in the figure. In the figure, A is the film prepared in Example 1, B is the film prepared in Comparative Example 1, C is the film prepared in Comparative Example 2, and D is the film prepared in Comparative Example 3.

[0031] Figure 5 The antibacterial properties of the films prepared in Example 1 and Comparative Examples 1 to 3 against Staphylococcus aureus are shown. In this example, A is the film prepared in Example 1, B is the film prepared in Comparative Example 1, C is the film prepared in Comparative Example 2, and D is the film prepared in Comparative Example 3. Detailed Implementation

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0034] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0035] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0036] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0037] The materials and equipment used in this invention were sourced as follows: Montmorillonite was purchased from Sigma-Aldrich Trading Co., Ltd. (Shanghai, China); Polyhexamethylene guanidine hydrochloride was purchased from Jiangsu Chentong Biotechnology Co., Ltd. (China); Poly(butylene adipate / terephthalate) was purchased from Jinhui Zhaolong (Shanxi, China); Corn starch was purchased from Yuanye Biotechnology Co., Ltd. (Shanghai, China); Epoxidized soybean oil was purchased from Maclean Biochemical Technology Co., Ltd. (Shanghai, China); Castor oil was purchased from Maclean Biochemical Technology Co., Ltd. (Shanghai, China); Palm oil was purchased from Maclean Biochemical Technology Co., Ltd. (Shanghai, China); Glycerin was purchased from Maclean Biochemical Technology Co., Ltd. (Shanghai, China); The high-speed mixer was an 8L, commercial 1800W model, purchased from JD.com under the Hanjia Ous brand; The twin-screw extruder was a Rheomex model. PTW16, purchased from Thermo Fisher Scientific (USA); AKPL-100 cold-cut pelletizer, purchased from Nanjing Keya Chemical Equipment Co., Ltd. (China); CSJ-5 blown film machine, purchased from Shanghai Changkai Electromechanical Technology Co., Ltd. (China); and Feiyue NZ-1 winding machine.

[0038] Example 1

[0039] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0040] (2) Corn starch was dried at 70℃ for 6 hours (starch has good water absorption, and drying pretreatment can remove excess water). The dried starch, glycerin, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time is 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain the premix. The mass ratio of dried starch, glycerin and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix.

[0041] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0042] (4) Granules are blown into film in a blown film machine. The operating temperature of the blown film machine is set to 130℃, 140℃, 145℃, 145℃, 140℃, and 130℃. The speed of the blown film machine is 80 rpm, and the traction speed of the blown film machine is 3. The resulting film (e.g.) Figure 1(A) is divided into sections with a width of 5mm to obtain slit-film fibers (e.g., ...). Figure 1 (C)

[0043] (5) Use a winding machine to twist the split film fibers into a thread with a twist count of 50.

[0044] Example 2

[0045] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0046] (2) Corn starch was dried at 60℃ for 7 hours. The dried starch, glycerin, castor oil and premix were mixed using a high-speed mixer (5 minutes each time, 5 times in total). Then poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerin and castor oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix, and the amount of poly(adipate) / butylene terephthalate added was calculated as 30% of the premix.

[0047] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The working temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 100 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0048] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 60 rpm and the traction speed of the blown film machine is 3. The film is obtained and cut into 4 mm widths to obtain split film fibers.

[0049] (5) Use a winding machine to twist the split film fibers into a thread with a twist count of 50.

[0050] Example 3

[0051] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0052] (2) Corn starch was dried at 80℃ for 5 hours. The dried starch, glycerin, palm oil and premix were mixed using a high-speed mixer (5 minutes each time, 5 times in total). Then poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerin and palm oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix, and the amount of poly(adipate) / butylene terephthalate added was calculated as 40% of the premix.

[0053] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The working temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 140 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0054] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 100rpm and the traction speed of the blown film machine is 3. The film is obtained and cut into 6mm widths to obtain split film fibers.

[0055] (5) Use a winding machine to twist the split film fibers into a thread with a twist count of 50.

[0056] Comparative Example 1

[0057] (1) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and polyhexamethylene guanidine hydrochloride were mixed using a high-speed mixer (5 minutes each time, 5 times in total). Then poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of poly(adipate) / butylene terephthalate added was calculated as 1% of the mass of the premix, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the mass of the premix.

[0058] (2) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0059] (3) Granules are blown into film in a blown film machine. The operating temperature of the blown film machine is set to 130℃, 140℃, 145℃, 145℃, 140℃, and 130℃. The speed of the blown film machine is 80 rpm, and the traction speed of the blown film machine is 3. The resulting film (e.g.) Figure 1 (B) is divided into sections with a width of 5mm to obtain split-film fibers.

[0060] Comparative Example 2

[0061] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0062] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (5 minutes each time, 5 times in total). Then poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.5% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0063] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0064] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and then cut into 5 mm widths to obtain split film fibers.

[0065] Comparative Example 3

[0066] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0067] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerin, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time was 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerin and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 1% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0068] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0069] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and then cut into 5 mm widths to obtain split film fibers.

[0070] Comparative Example 4

[0071] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0072] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time was 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0073] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0074] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and then cut into 1 cm widths to obtain split film fibers.

[0075] Comparative Example 5

[0076] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0077] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time was 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0078] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0079] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and then cut into 2cm widths to obtain split film fibers.

[0080] Comparative Example 6

[0081] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0082] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time was 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0083] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0084] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and then cut into 3cm wide sections to obtain split film fibers.

[0085] Comparative Example 7

[0086] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0087] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time was 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0088] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0089] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and cut into 5mm widths to obtain split film fibers.

[0090] (5) Use a winding machine to twist the split film fiber into a thread with a twist count of 100.

[0091] Comparative Example 8

[0092] (1) Montmorillonite and polyhexamethylene guanidine hydrochloride were mixed to obtain a preliminary mixture;

[0093] (2) Corn starch was dried at 70℃ for 6 hours. The dried starch, glycerol, epoxidized soybean oil and the initial mixture were mixed using a high-speed mixer (each mixing time was 5 minutes, and a total of 5 mixing times). Then, poly(adipate) / butylene terephthalate was added to obtain a premix. The mass ratio of dried starch, glycerol and epoxidized soybean oil was 10:3:0.5. The amount of montmorillonite added was calculated as 0.3% of the premix mass, the amount of polyhexamethylene guanidine hydrochloride added was calculated as 1% of the premix mass, and the amount of poly(adipate) / butylene terephthalate added was calculated as 50% of the premix mass.

[0094] (3) The premix is ​​heated and plasticized in a twin-screw extruder. The operating temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 120 rpm. Granulation is carried out in a pelletizer. The pelletizing speed is 180 rpm to obtain pellets.

[0095] (4) Granules are blown into a film in a blown film machine. The working temperature of the blown film machine is set at 130℃, 140℃, 145℃, 145℃, 140℃ and 130℃. The speed of the blown film machine is 80 rpm and the traction speed of the blown film machine is 3. The film is obtained and cut into 5mm widths to obtain split film fibers.

[0096] (5) Use a winding machine to twist the split film fiber into a thread with a twist count of 200.

[0097] Experimental Example 1

[0098] Infrared spectra of montmorillonite, the film prepared in Example 1, and the films prepared in Comparative Examples 1 to 3 were determined. Mechanical properties of the film prepared in Example 1 and the films prepared in Comparative Examples 1 to 3 were determined. Antibacterial properties of the film prepared in Example 1 and the films prepared in Comparative Examples 1 to 3 were determined.

[0099] like Figure 2 The image shows the infrared spectra of montmorillonite, the film prepared in Example 1, and the films prepared in Comparative Examples 1 to 3. (3200–3300 cm⁻¹) -1 The characteristic peak at this location is the hydroxyl peak of the interlayer water in montmorillonite, which can be obtained from... Figure 2 As can be seen from the examples, after adding montmorillonite to the starch-based materials in Examples 1, 2, and 3, the characteristic peak of hydroxyl groups shifted towards higher wavenumbers. This is because the interaction between polyhexamethylene guanidine hydrochloride and montmorillonite in the system affected the interlayer spacing, resulting in a shift in the characteristic peak of interlayer water.

[0100] like Figure 3 The figures shown are mechanical property diagrams of the thin film prepared in Example 1 and the thin films prepared in Comparative Examples 1 to 3. Figure 3 As can be seen, the tensile properties were best when the montmorillonite content was 0.3 wt% as shown in Example 1. However, the mechanical properties decreased with the increase of montmorillonite content (Comparative Examples 2 and 3). This is because montmorillonite interacts with the matrix, thereby achieving effective load transfer. However, with the increase of montmorillonite content, it agglomerates in the matrix, resulting in poor dispersibility and thus a decrease in performance.

[0101] like Figure 4 and Figure 5 The figure shown is a graph illustrating the antibacterial properties of the film prepared in Example 1. Figure 4 and Figure 5 As can be seen, the films prepared in Example 1 and Comparative Examples 1-3 all exhibit inhibitory effects against *Escherichia coli* and *Staphylococcus aureus*, with a more pronounced inhibitory effect against *Staphylococcus aureus*. This may be because the cell wall structure of *Staphylococcus aureus* is relatively simple, allowing guanidine salt polymers to more easily bind to teichoic acid and peptidoglycan on its cell wall surface, disrupting cell wall integrity and leading to bacterial death. In contrast, the outer membrane structure of *E. coli* effectively prevents the adsorption and penetration of montmorillonite, resulting in a relatively weaker antibacterial effect. Therefore, the antibacterial properties can reduce biocontamination of the material.

[0102] The mechanical properties of the slit-film fibers prepared in Example 1 and the slit-film fibers prepared in Comparative Examples 4 to 6 were measured.

[0103] Table 1. Mechanical properties of the split-film fibers prepared in Example 1 and Comparative Examples 4 to 6.

[0104] Group Tensile strength (MPa) Young's modulus (MPa) Example 1 9.19 112.44 Comparative Example 4 7.46 83.85 Comparative Example 5 6.49 77.33 Comparative Example 6 5.36 69.83

[0105] As shown in Table 1, the split-film fiber has good mechanical properties when the width is 5 mm and relatively small (Example 1).

[0106] The mechanical properties of the wires prepared in Example 1, Comparative Example 7, and Comparative Example 8 were determined.

[0107] Table 2 Mechanical properties of the threads prepared in Example 1, Comparative Example 7, and Comparative Example 8

[0108] Group Fracture strength (N) Elongation at break (%) Example 1 3.61 695.45 Comparative Example 7 3.21 662.83 Comparative Example 8 3.31 699.51

[0109] As shown in Table 2, twisting has little effect on the mechanical properties of split-film fibers. This is because the twist used is close to or lower than the value that can affect the properties, so the internal interface structure of the split-film fibers is not significantly affected, and thus the mechanical properties do not change significantly on a macroscopic scale.

[0110] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing an antibacterial starch-based split-film fiber for degradable fishing nets, characterized by, Includes the following steps: (1) Layered nanomaterials are mixed with guanidine salt polymers to obtain a preliminary mixture; (2) Starch drying, the dried starch, glycerin, epoxy vegetable oil and the initial mixture obtained in step (1) are mixed, and then poly(butylene adipate) terephthalate is added to obtain the premix; (3) The premix obtained in step (2) is heated and plasticized, then granulated to obtain granules; (4) The granules obtained in step (3) are blown into a film to obtain a thin film, which is then slit to obtain split film fibers; The layered nanomaterial mentioned in step (1) is montmorillonite; the guanidine salt polymer mentioned in step (1) is polyhexamethylene guanidine hydrochloride; The mass ratio of the dried starch, glycerol and epoxy-based vegetable oil in step (2) is 10:3:0.5; the mass of the layered nanomaterial in step (1) accounts for 0.3% of the mass of the premix; the mass of the guanidine salt polymer in step (1) accounts for 1% of the mass of the premix; and the mass of the poly(adipate) / butylene terephthalate in step (2) accounts for 30% to 50% of the mass of the premix.

2. The preparation method according to claim 1, characterized in that, The drying temperature in step (2) is 60~80℃, and the drying time is 5~7h.

3. The preparation method according to claim 1, characterized in that, The starch mentioned in step (2) is corn starch; the epoxidized vegetable oil mentioned in step (2) is one of epoxidized soybean oil, castor oil and palm oil.

4. The preparation method according to claim 1, characterized in that, The heating and plasticizing described in step (3) is carried out in a twin-screw extruder. The working temperature of the twin-screw extruder is set to 130℃, 130℃, 140℃, 140℃, 145℃, 145℃, 145℃, 140℃, 130℃, and 130℃. The screw speed of the twin-screw extruder is 100~140 rpm.

5. The preparation method according to claim 1, characterized in that, The pelletizing speed in step (3) is 180 rpm.

6. The preparation method according to claim 1, characterized in that, In step (4), the blown film is blown in a blown film machine. The working temperature of the blown film machine is set to 130℃, 140℃, 145℃, 145℃, 140℃, and 130℃. The speed of the blown film machine is 60~100rpm and the traction speed of the blown film machine is 3. The width of the segmentation process in step (4) is 4~6mm.

7. The slit-film fiber prepared by the preparation method according to any one of claims 1 to 6.

8. The application of the split-film fiber as described in claim 7 in the preparation of a biodegradable antibacterial fishing net.

Citation Information

Patent Citations

  • Preparation method, product and application of nano-montmorillonite reinforced starch-based biodegradable film blowing material

    CN112405931A

  • Long-acting antibacterial degradable polyester food packaging film and preparation method thereof

    CN114907676A